2016
DOI: 10.1186/s12884-016-1041-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hyperemesis gravidarum and small-for-gestational-age in the Japanese population: the Japan Environment and Children’s Study (JECS)

Abstract: BackgroundSmall-for-gestational-age in infancy is a known risk factor not only for short-term prognosis but also for several long-term outcomes, such as neurological and metabolic disorders in adulthood. Previous research has shown that severe nausea and vomiting in early pregnancy (NVP) and hyperemesis gravidarum, which is an extreme form of NVP, represent risk factors for small-for-gestational-age birth. However, there is no clear consensus on this association. Thus, in the present study, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
(26 reference statements)
1
19
0
3
Order By: Relevance
“…The means of maternal age, gestational age at birth, and birth weight were 30.6 ± 4.98 years, 39.0 ± 1.14 weeks, and 3051 ± 369.85 g, respectively. Results of the univariate analysis for birth weight, which accounted for confounding background and social factors, are shown in a table in the previous article [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The means of maternal age, gestational age at birth, and birth weight were 30.6 ± 4.98 years, 39.0 ± 1.14 weeks, and 3051 ± 369.85 g, respectively. Results of the univariate analysis for birth weight, which accounted for confounding background and social factors, are shown in a table in the previous article [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…After excluding missing data and premature birth, we analyzed the data of the remaining 8631 women who had singleton, full-term (≥37 weeks, but <42 weeks) pregnancies (Fig. 1 of the previous article [ 5 ]). The present study is based on the dataset of jecs-ag-ai-20131008, which was released in October 2013.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…(31) Another study showed an increased risk of SGA in women who had hyperemesis gravidarum during pregnancy, but studies on the effects of milder symptoms have shown either a protective effect of nausea and vomiting of pregnancy or no difference. (4,29,30) Of note, these studies all took place in high-income countries. On the other hand, studies in high-income settings have showed a signi cantly increased risk of LBW and SGA in women with hyperemesis gravidarum.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an increased risk of SGA in women who had hyperemesis gravidarum during pregnancy, but studies on the effects of milder symptoms have shown either a protective effect of NV of pregnancy or no difference. (4,24,25) However, these studies all took place in high-income countries. On the other hand, studies in high-income settings have showed a significantly increased risk of LBW and SGA in women with hyperemesis gravidarum.…”
Section: Discussionmentioning
confidence: 99%